Capsid-specific T-cell Responses to Natural Infections With Adeno-associated Viruses in Humans Differ From Those of Nonhuman Primates - Li, Hua (Nature Publishing Group, 2011)
Hepatic adeno-associated virus serotype 2 (AAV2)-mediated gene transfer failed to achieve sustained transgene product expression in human subjects. We formulated the hypothesis that rejection of AAV-transduced hepatocytes is caused by AAV capsid-specific CD8(+) T cells that become reactivated upon gene transfer. Although this hypothesis was compatible with clinical data, which showed a rise in circulating AAV capsid-specific T cells following injection of AAV vectors, it did not explain that AAV vectors achieved long-term transgene expression in rhesus macaques, which are naturally infected with AAV serotypes closely related to those of humans. To address this apparent contradiction, we tested human and rhesus macaque samples for AAV capsid-specific T cells by intracellular cytokine staining combined with staining for T-cell subset and differentiation markers. This highly sensitive method, which could provide a tool to monitor adverse T-cell responses in gene transfer trials, showed that AAV capsid-specific CD8(+) and CD4(+) T cells can be detected in blood of naturally infected humans and rhesus macaques. They are present at higher frequencies in rhesus macaques. Furthermore, T cells from humans and rhesus macaques exhibit striking differences in their differentiation status and in their functions, which may explain the disparate duration of AAV-mediated gene transfer in these two species.